2022
DOI: 10.1177/13591053211067100
|View full text |Cite
|
Sign up to set email alerts
|

Keep your distance: Different roles for knowledge and affect in predicting social distancing behavior

Abstract: The current study examines predictors of social distancing behavior across populations (students and community members) and across time in the early months of the COVID-19 pandemic, focusing on two factors commonly associated with risk perception and prevention: knowledge and affect. Results showed that, despite similar levels of social distancing, student distancing was predicted only by feelings of threat about COVID-19, whereas community distancing was predicted by both feeling informed and threatened. Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…(However, it is worth mentioning that the perception of the risk of personally experiencing an adverse life event is generally underestimated relative to the perceived risk of other people experiencing such events [ Sharot, 2011 ] and it has been found that the perceived risk of contracting COVID is no exception to this optimism bias [ Wise et al, 2020 ].) Interestingly, as far as the specific roles of knowledge about COVID-19 and of COVID-related affects in disease avoidance are concerned, a recent study has shown that social-physical distancing in students was (positively) predicted by affect (feeling threatened by COVID-19), whereas for members of the wider community (an older and a more diverse population), distancing was predicted by both affect (e.g., how concerned they were about catching COVID-19) and knowledge (e.g., number of days officially recommended for self-quarantining) ( Choi et al, in press ).…”
Section: Aim Of the Present Studymentioning
confidence: 99%
“…(However, it is worth mentioning that the perception of the risk of personally experiencing an adverse life event is generally underestimated relative to the perceived risk of other people experiencing such events [ Sharot, 2011 ] and it has been found that the perceived risk of contracting COVID is no exception to this optimism bias [ Wise et al, 2020 ].) Interestingly, as far as the specific roles of knowledge about COVID-19 and of COVID-related affects in disease avoidance are concerned, a recent study has shown that social-physical distancing in students was (positively) predicted by affect (feeling threatened by COVID-19), whereas for members of the wider community (an older and a more diverse population), distancing was predicted by both affect (e.g., how concerned they were about catching COVID-19) and knowledge (e.g., number of days officially recommended for self-quarantining) ( Choi et al, in press ).…”
Section: Aim Of the Present Studymentioning
confidence: 99%
“…For example, some have suggested that prophylactic measures such as vaccination could have unintended consequences, such as “a false sense of security that can lead to neglecting other essential measures” (World Health Organization, 2020) and asking “as vaccines roll out, will risky behavior increase?” (Doheny, 2021). When questions arise about potential psychological consequences, they almost exclusively target self‐directed reactions, such as risky decision‐making and behavior, of those individuals using preventive measures (e.g., Ackerman et al., 2021; Choi et al., 2022).…”
mentioning
confidence: 99%
“…(Doheny, 2021). When questions arise about potential psychological consequences, they almost exclusively target self-directed reactions, such as risky decision-making and behavior, of those individuals using preventive measures (e.g., Ackerman et al, 2021;Choi et al, 2022).…”
mentioning
confidence: 99%